Assessing Fiscal Implication of the Recent Changes in Poverty Lines and Revision of Allocation Norms of Capital Expenditures and Resources for Targeted Programs - World Bank (Washington, DC, 2013)
There have been important changes in the budgeting process in Vietnam since 2006 when the government of Vietnam instituted a revolutionary reform in the management and allocation of the state budget. For the period of 2007-2010, the norms include ethnic minority population data, and poverty rates. The purpose of this research assignment is to describe the evolution of budgeting mechanisms in recent years, in association with capital expenditure transferred from central to provincial budgets. This report focuses on changes in the budgeting process and allocation norms. It is also assesses whether these recent changes are pro-poor, and how they would affect availability of resources for the national targeted programs.